2018
DOI: 10.3390/w10091279
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Hydrological Extremes in the Yangtze River Basin with an Ensemble of Regional Climate Simulations

Abstract: This paper estimates the likely impacts of future climate change on streamflow, especially the hydrological extremes over the Yangtze River basin. The future climate was projected by the Coordinated Regional Climate Downscaling Experiment in East Asia (CORDEX-EA) initiative for the periods 2020–2049 under two representative concentration pathways (RCP) 4.5 and 8.5 emission scenarios. The bias corrected outputs from five regional climate models (RCMs) were used in conjunction with the variable infiltration capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 85 publications
5
18
0
Order By: Relevance
“…Previous studies have mainly used climate conditions predicted by global climate models (GCMs) to drive hydrological models to study the responses of UYRB hydrology to climate change 18 26 . However, few studies have investigated the hydrological changes in the UYRB under climate change using a coupling model based on the RegCM4 and variable infiltration capacity (VIC) models 27 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mainly used climate conditions predicted by global climate models (GCMs) to drive hydrological models to study the responses of UYRB hydrology to climate change 18 26 . However, few studies have investigated the hydrological changes in the UYRB under climate change using a coupling model based on the RegCM4 and variable infiltration capacity (VIC) models 27 29 .…”
Section: Introductionmentioning
confidence: 99%
“…RegCM has been applied to the UYRB as an effective tool for assessing and projecting hydroclimatic conditions 27 – 31 , but it remains challenging to accurately assess and project climate changes in the basin. Gao et al 31 found that, according to a coupling model of RegCM2 and CSIRO R21L9, precipitation in most regions of the YRB will increase in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In such a scenario, an understanding of river hydrology and its evolution within future climatic conditions is of immense significance for water resources management and sustainable development. Previous studies show that most climate variables, with the exception of temperature, are expected to experience varying trends in time and space, as does the flow regime 7 11 . However, it is crucial to note that most global scale studies are often conducted at a spatial resolution which is too coarse to capture local climatic phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The increased variability of rainfall means more intense short-period rainfall events and maximum stream flows. This can increase flooding events (Wang & Zhang, 2011;Gu et al, 2015;Yu et al, 2018;Gu et al, 2018).…”
Section: Impacts On the Yangtze River Hydrologymentioning
confidence: 99%